2014
DOI: 10.1097/bot.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Static Electronic Advertising Signs on Road Safety

Abstract: As technology continues to advance, the outdoor advertising industry is taking advantage of electronic signs, some of which are static electronic signs (SES), with the ability to automatically change the message shown on the sign at regular intervals. Studies indicate that SES has a negative impact on the drivers' visual attention and on vehicle control. However, the actual effects of the SES on the number of collisions have been difficult to prove conclusively. The objective of this article is to generate a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…A before and after statistical analysis with control groups was applied on road sites of different characteristics in Athens, Greece, to investigate the correlation Journal of Transportation Technologies between the placement or removal of advertising signs and road accident occurrence; it shows no statistical correlation between road accidents and advertising signs in none of the examined sites [16]. A similar study, before and after with the control group, in Toronto, Canada, suggested that static electronic signs do not impact road safety along the adjacent roadway sections [17]. However, crash risks increase near static digital billboards [18].…”
Section: Roadside Advertisement External Source Of Distractionmentioning
confidence: 99%
“…A before and after statistical analysis with control groups was applied on road sites of different characteristics in Athens, Greece, to investigate the correlation Journal of Transportation Technologies between the placement or removal of advertising signs and road accident occurrence; it shows no statistical correlation between road accidents and advertising signs in none of the examined sites [16]. A similar study, before and after with the control group, in Toronto, Canada, suggested that static electronic signs do not impact road safety along the adjacent roadway sections [17]. However, crash risks increase near static digital billboards [18].…”
Section: Roadside Advertisement External Source Of Distractionmentioning
confidence: 99%
“…The second factor can be controlled by legislative solutions. The message design includes: movement, light emission, shape of the carrier, and location (Crundall et al 2006;Izadpanah et al 2014;Smiley et al 2005), all of which engage bottom-up attention, as well as the content of advertisements which activates top-down processing (Shinoda et al 2001).…”
Section: Examining the Mechanisms Used In Ads Underlying The Distractionmentioning
confidence: 99%
“…This leads to the question as to how roadside advertisements influence road safety. Statistical analysis of the number of accidents and behaviour changes reveal some decrease in driver effectiveness in the presence of roadside advertising [1,2], however, other data suggest the contrary [3]. Driving simulator studies show that in the context of roadside advertising, drivers show more behaviours resulting from inattention [4], memorize traffic signs less effectively and feel more tired [5][6][7], but in each of the studies, some other indicators of driving effectiveness remain unaffected.…”
Section: Introductionmentioning
confidence: 95%